Hydrological Alterations and Soil Microbial Responses Under Prolonged Irrigation and Salinity Stress - Shakhobiddin Turdimetov; Mokhinur Musurmanova; Gulom Jurayev; Berdiyor Ixtiyor Ogli Omonboyev; Mohamed Fawzy Ramadan; Muhammad Ishtiaq Ali; Salman Majeed; Muhammad Rizwan Khan; Trobjon Makhkamov; Adnan Amin (Irrigation and Drainage, 2026)
The Mirzachol Oasis is one of the most important agroecological regions in Uzbekistan and has been subject to six decades of intensified irrigation, resulting in significant hydrological and soil changes. The impact on microbial communities below the surface is less well studied than its impact on the surface, but both affect soil health. This study addresses this gap by examining microbial communities, soil physicochemical parameters and historical irrigation data from 1960–2020 across six separate plots, including protected and irrigated plots. The results show that, due to organic matter accumulation and cultivation, extended irrigation increased microbial diversity and biogenicity in nonsaline soils (such as the U. Nasir and Yangi Hayot massifs). Nevertheless, secondary salinization disrupted nutrient cycling by suppressing functional microbial guilds, such as nitrifiers and cellulose‐degrading bacteria, in irrigated zones (e.g., the M. Uzoqov and Pakhtakor massifs). The salinization legacy reduces ecosystem stability, while older irrigated soils exhibit greater microbial resilience than recently irrigated or protected lands. Microbial activity was further influenced by seasonal variations, pH changes and groundwater fluctuations; salinity exacerbated reductions in fungal and actinomycete populations.